Enhancement of the Forming Limits for Orbital Formed Tailored Blanks by Local Short-term Heat Treatment - Hetzel, Andreas; Merklein, Marion; Lechner, Michael (Procedia Manufacturing, 2020)
Nowadays, the manufacturing industry faces opposing challenges like a reduction of carbon dioxide on the one hand and on the other hand an increasing weight due to higher safety standards and additional functions. Concepts like lightweight design and functional integration are essential to ensure a sustainable and individual mobility. Gear systems consist of multi-functional parts with a varying sheet thickness and different geometric elements. Since conventional manufacturing processes like shearing are reaching their limits due to complexity and a lack in efficiency, the application of Tailored Blanks is a promising approach to meet these requirements. Manufactured by orbital forming, these process-adapted blanks dispose a high material efficiency. A tumbling motion of the upper punch enables the material distribution, realizing functional components with different material thickenings. The substitution of steel by aluminum is a common approach to meet the demands of lightweight construction. However, the use of aluminum results in a decreased formability at a constant level of strength. In order to enhance the local forming limits, a short-term heat treatment can be applied, reducing the materials' strength, whereas the untreated areas still offer the initial properties. To transfer the results of fundamental research in Sheet-Bulk Metal Forming with conventional steel to the use of lightweight material, the precipitation hardenable aluminum alloy EN AW 6016 is investigated in an orbital forming process. Since the formability of aluminum is limited and the material flow during the process is three-dimensional, different heat treatment strategies are applied to a rotational-symmetric Tailored Blank and the resulting components are investigated regarding their geometry and mechanical properties. To increase the geometric complexity with regard to an industrial application, the transferability to a cyclic-symmetric layout is analyzed. To evaluate the potential of the heat treatment, the treated components are compared to Tailored Blanks manufactured without heat treatment.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Aluminum EN AW 6016; Heat Treatment; Lightweight Design; Orbital Forming; Tailored Blanks